How does international trade affect household welfare? - Beyza Ural Marchand (IZA World of Labor, 2017)
Imported products tend to have lower prices than locally produced ones for a variety of reasons, including lower labor costs and better technology in the exporting country. The reduced prices may lead to wage losses for individuals who work in the production of a local version of the imported item. On the other hand, lower prices may be beneficial to households if the cheaper product is in their consumption basket. These welfare gains through consumption, on average, are found to be larger in magnitude than the wage effect for some developing countries.
Keywords: D31; F14; O12; O15; 330; international trade; household welfare; consumption; wages